Move that Body! En introduktion til Richard Middleton’s gesture-teori - Ihlemann, Lisbeth (Danish Yearbook of Musicology, 1994)
Move that Body! An introduction to Richard Middelton’s theory of gesture An often made connection is that between rock music and the body. While there is no doubt that listening to rock music often makes the body move, and that this is crucial in the experience of rock, several problems arise when dealing with this subject in terms of a musicological analysis. In some of his recent works Richard Middleton proposes that the notion of musical gesture should be taken into account when working analytically with the music-body connection. In this article I agree with the notion of gesture. Through a gestural analysis of the refrain in Felix' It Will Make me Crazy, I attempt to sketch out some of the diffkulties that must be dealt with in this connection. They are, among others, problems of how to present the analysis, because words and scores often fail in reproducing the musical gestures. In addition problems arise regarding the role of the analyst, who now has to participate in the reception process. Despite these problems, I propose that musical gesture can serve as a very promising analytical concept.